PEMANFAATAN EKSTRAK JAMUR Coriolus versicolor UNTUK MENINGKAT KAN JUMLAH TOTA L LEUKOSIT DAN MAKROFA G PADA TIKUS PUTIH WISTAR SETELAH PEMAPARAN 2-METHOXYETHANOL - Sri Puji Astuti Wahyuningsih (The East Java Biological Society, 2008)
The aim of this research was to increase sum of total rat’s leucocytes and macrophages using Coriolus versicolor exposure 2-Methoxythanol (2-ME). Coriolus versicolor extract have been primary active compounds are polysaccharide krestin (PSK). This compound PSK contains of ß-glucan. The immune cells had b-glucan receptor. From this reason, Coriolus versicolor extract could increase of immune system after exposed 2-ME. This research used 30 of 3–4 month female rats, and they were divided into 5 groups. K (control), P1 (exposed by 2-ME), P2 (administered with Coriolus versicolor extract before exposed by 2-ME), P3 (administered with Coriolus versicolor extract after exposed by 2-ME), P4 (administered with Coriolus versicolor extract before and after exposed by 2-ME). Coriolus versicolor extract used dose of 300 mg/kg body weight was given with gavage. 2-ME dose of 11 mmol/kg body weight was given with injection at cavum peritoneum. Number on leucocytes and macrophages counted by using Haemocytometer Improved Neubauer. The data was analyzed with ANOVA, further more if any differences were analyzed with LSD. Result of this study showed that (1) P1 decreased on the total number of leucocytes if compared with K, but increased on the total number of macrophage. (2) P2, P3, and P4 increased the total number of leucocytes and macrophage. Suggestion that can be proposed from this research was Coriolus versicolor extract can repair and increase immune system.